2022
DOI: 10.1097/corr.0000000000002241
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Clinical Benefit of Common Orthopaedic Procedures as Assessed by the PROMIS Versus Other Validated Outcomes Tools?

Abstract: Background Patient-reported outcome measures (PROMs), including the Patient-reported Outcomes Measurement Information System (PROMIS), are increasingly used to measure healthcare value. The minimum clinically important difference (MCID) is a metric that helps clinicians determine whether a statistically detectable improvement in a PROM after surgical care is likely to be large enough to be important to a patient or to justify an intervention that carries risk and cost. There are two major categories of MCID ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…We think the likelihood of this is very low because we strictly adhered to Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines for our comprehensive three-database search. After the current study was accepted for publication, but before final publication, Karhade et al [28] published a retrospective study examining MCID thresholds and attainment for PROMIS scores. Because that study was published after our search dates, it was not included in this analysis.…”
Section: Discussionmentioning
confidence: 99%
“…We think the likelihood of this is very low because we strictly adhered to Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines for our comprehensive three-database search. After the current study was accepted for publication, but before final publication, Karhade et al [28] published a retrospective study examining MCID thresholds and attainment for PROMIS scores. Because that study was published after our search dates, it was not included in this analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Although the SF‐36 has not been specifically validated in orthopedic oncology patients, an MCID has been reported for this tool 72,73 . PROMIS has been validated in several solid malignancies, 74 benign orthopedic conditions, 75 in addition to metastatic spine tumors 76 and bone and soft tissue tumors 77 . Two studies have reported MCID for PROMIS following surgical management in patients with benign and malignant soft tissue tumors 52 and lower extremity metastases 78 .…”
Section: Limitationsmentioning
confidence: 99%
“…Most would agree that anchor-based scores are preferable, but the lack of these scores for commonly performed orthopaedic procedures has driven the need for distribution-based approaches. The article by Karhade et al [1] clearly indicates the complexity of the issue. PROMIS, PROMs, MCID, anchor-based, distribution-based, one-third to one-half standard deviation, minimal detectable change (MDC) 50, MDC 95, and MDC 99 are just some of the terms and abbreviations used in the paper.…”
Section: Where Do We Need To Go?mentioning
confidence: 99%
“…An article in this month's Clinical Orthopaedics and Related Research ® by Karhade et al [1] describes this issue-or maybe "confusion" is a better word-exceedingly well. They compared the achievement of the minimum clinically important difference (MCID) for common orthopaedic procedures using the Patient-Reported Outcomes Measurement Information System (PROMIS) compared with other patient-reported outcome measures (PROMs), called legacy PROMs because they have been used for many years.…”
mentioning
confidence: 99%